LOGO DESIGN WERDHA PRIYAMITRA ELDERLY GROUP NORTH KUTA DISTRICT - I Made Jayadi Waisnawa; Toddy Hendrawan Yupardhi (Yayasan Sinergi Widya Nusantara, 2023)
Purpose: The elderly are a part of society that deserves to be honoured. Various service activities have been carried out during the productive age. The logo design requested by the Werdha Priyamitra elderly group is a tribute to its role in mobilizing other elderly people in North Kuta District. Research methods: The method in designing the logo of the Werdha Priyamitra elderly group was carried out with the stages of observation, interviews, digital literature review and evaluation. Observation is intended to explore the activities of the elderly group. The interview is a process of extracting deeper data from the beginning of its establishment until its existence in 2023. Digital literature review to gain knowledge and inspiration in logo design. Findings: Every design stage constantly evaluates by the management of the Werdha Priyamitra elderly group so that the logo design is as expected. Based on the final logo design results, design elements in lines, fields, and colours represent the culture and activities of the Werdha Priyamitra elderly group. Implications: These design elements are supported by text that contains the slogan of the Werdha Priyamitra elderly group. The logo design is made by considering the proportion of design elements and text to keep the intensity of complexity manageable.